Implementation Of Information System Digitization And Accounting Software Implementation At Umkm Niana Salon - Ayu Lestari, Rahma; Hurriyaturrohman; Rizqi, Muhammad Nur (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This research is motivated by the limitations of the community in knowing and operating information systems. Niana Salon requires an accounting data processing process that can assist its activities in managing financial reports more effectively and efficiently in order to obtain more optimal results in preparing financial reports. The purpose of this study is to implement Niana Salon's financial reports on a smartphone-based application system, namely the SME-Finance accounting application. The accounting recording method at Niana Salon is the accrual basis recording method, and Niana Salon still uses manual recording, which is prone to recording errors. Researchers implemented the application of Accounting Software to UMKM Niana Salon. There are several stages in the research method for a case study of Niana Salon's financial reports based on an Android smartphone, namely planning, data collection, data processing, and data migration to the SME-Finance accounting application. The SME-Finance accounting application is very helpful in Niana Salon's daily recording process because by using the SME-Finance accounting application, Niana Salon's financial report information is faster and more precise. In addition, this can minimize manual recording errors.